Making friends organizing your library's friends group (The Wilson video resource collection, 1987)
Explains preliminary planning, formation of a steering committee, recruitment of members and officers, and setting up agenda for organizational meeting for a friends group. It shows that friends can be helpful in fund raising, sponsoring programs, providing volunteer services to augment what's provided by paid staff, citizen lobbying.